Pengaruh Environmental Responsibility dan Social Innovation terhadap Business Performance dengan Corporate Reputation sebagai Variabel Mediasi: Studi pada PT Olahkarsa Inovasi Indonesia - Peggy Rozzah; Eric Harianto (SAFE-Network, 2026)
Sustainability practices are increasingly assessed by their ability to generate business value, particularly in service-based organizations whose performance depends on credibility and stakeholder trust. In ESG consulting firms, environmental and social initiatives may not directly translate into business outcomes unless they strengthen how stakeholders perceive the organization. This study examines the influence of Environmental Responsibility and Social Innovation on Business Performance, with Corporate Reputation as a mediating variable, at PT Olahkarsa Inovasi Indonesia. A quantitative explanatory design was applied using a census approach involving all 82 employees of the company. Data were collected through a structured questionnaire and analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). The results show that Environmental Responsibility does not have a direct effect on Business Performance, but significantly improves Corporate Reputation. Social Innovation has a significant positive effect on both Corporate Reputation and Business Performance. Corporate Reputation also significantly affects Business Performance and mediates the relationships between Environmental Responsibility, Social Innovation, and Business Performance. These findings indicate that sustainability initiatives create business value when they are recognized by stakeholders as credible organizational commitments. For ESG consulting firms, reputation serves as a strategic mechanism that connects sustainability practices with business performance through trust, legitimacy, and perceived organizational reliability.